Automating intellectual freedom: Artificial intelligence, bias, and the information landscape. (October 2022) - Smith, Catherine
Anxieties over automation and personal freedom are challenging libraries' role as havens of intellectual freedom. The introduction of artificial intelligence into the resource description process creates an opportunity to reshape the digital information landscape—and loss of trust by library users. Resource description necessarily manipulates a library's presentation of information, which influences the ways users perceive and interact with that information. Human catalogers inevitably introduce personal and cultural biases into their work, but artificial intelligence may perpetrate biases on a previously unseen scale. The automation of this process may be perceived as a greater threat than the manipulation produced by human operators. Librarians must understand the risks of artificial intelligence and consider what oversight and countermeasures are necessary to mitigate the harm to libraries and their users before ceding resource description to artificial intelligence in place of the "professional considerations" the IFLA Statement on Libraries and Intellectual Freedom calls for in providing access to library materials.